Future Arabic Translator and Chat Gpt-3 Change Work Dynamics in The Translation Profession: Students' Voices - Ahmad Habibi Syahid; Mochamad Mu'izzuddin; Yuyun Rohmatul Uyuni; Nuroh Nuroh (Universitas Islam Negeri Palangka Raya, 2025)
This research describes the interaction between the most advanced language technology, ChatGPT-3, and the translation profession from a student's perspective. In an era of technology that increasingly influences various aspects of life, one of which is translation, this research aims to explore students' views and experiences regarding the use of language technology such as ChatGPT-3 in the context of translator work. Through a qualitative approach, this research gathered insights into how students interested in the translation profession view the changes brought by technology. Data collection was carried out through in-depth interviews with students from various academic backgrounds who had an interest in Arabic translation. The results of this research provide an in-depth understanding of students' perceptions of the role of technology in the translation profession, the challenges they identify, and the opportunities they see. This research provides a new perspective on the evolving dynamics between technology and the translation profession, particularly from the perspective of the younger generation who will shape the future of translation.